Impact of Using Whatsapp Application in the English Learning in Junior High School - Munir, Munir; Rau, Rahmawati (Celebes Journal of Language Studies, 2022)
The purpose of this study was to find out how to the teacher implement the WhatsApp application as a digital communication tool for learning English in junior high school and its impact on students. This study used a qualitative descriptive method and was conducted in Pangkep Junior High School, South Sulawesi, as many as 21 students from class VIII C and 1 English teacher were selected as research subjects through random sampling techniques. Data obtained from Observation, Interview and Documentation. The results obtained from the data analysis are 1) The implementation of the teacher when using the WhatsApp application with 3 indicators such as preparation for the creation of a WhatsApp group, implementation, namely sending file materials, and evaluation, namely providing evaluations and assignments to students. 2) the impact on students by learning to use the WhatsApp application, namely the positive impact: being able to do assignments anywhere, easy to understand the material given, negative impact: unable to ask questions directly, interaction with students is less established.